Frozen section evaluation of sentinel lymph nodes in breast carcinoma: a retrospective analysis - Russo, Leonardo (Ecancermedicalscience, 2017)
OBJECTIVE: To determine the false-negative rate, sensitivity, and diagnostic accuracy of the frozen section analysis of the sentinel lymph node (SLN) biopsy in early-stage breast cancer compared to the definitive section and to identify the factors that could be associated with the appearance of false-negative cases. Secondarily, to evaluate the pathological results of cases submitted to completion axillary lymph node dissection (ALND) for positive SLN. METHODS: We performed a five-year review of cases (2011–2015), including patients with early-stage breast cancer undergoing SLN biopsy, with frozen section evaluation and subsequent definitive pathological analysis. These results were compared to calculate the false-negative rate and the factors associated with it. The histopathological findings were also evaluated in patients submitted to completion ALND. RESULTS: A total of 281 patients were evaluated, identifying 18 cases with frozen section results as false negative (false-negative rate: 23.7%), and 55.5% of these cases were micrometastases. The false-negative rate in SLN with macrometastasis was 13.1% and for micrometastasis cases was 66.7% (p < 0.001). True-positive patients that were submitted to completion ALND had additional axillary lymph nodes with metastases in 28% of cases, whereas the group of false negatives had additional positive axillary lymph nodes in 40% of patients (p = 0.62). CONCLUSION: Frozen section analysis had a false-negative rate acceptable in SLN biopsy in our institution, and the micrometastasis in the SLN was the most important factor associated with the appearance of this phenomenon.